Introduction to “Shadows of state terrorism: impunity in Latin America” - McSherry, J. Patrice (Social justice, 1999)
Part of a special issue on state terrorism and impunity in Latin America. The writers introduce the articles included in this special issue, which they assert takes a fresh look at the issue of impunity some 10 to 15 years after the transitions to civilian government. They note that the articles seek to enhance understanding of the long-term effects of impunity and to illuminate the relationships among truth and memory, accountability and the rule of law, and democracy and social justice. They observe that the articles can be grouped into four sections: country cases that afford the reader a sense of the human impact of abuses and impunity; national and international responses to impunity, including legal remedies; historical antecedents of impunity; and book reviews and a photo essay.